ISLAM, CONSUMPTION, MIGRATION: EXPLORING ISLAMIC CONSUMERISM AND HALAL INDUSTRY IN A NON-MUSLIM SOCIETY - Kapustina, Ekaterina Leonidovna (History, Archeology and Ethnography of the Caucasus, 2024)
This article explores the anthropological dimensions of halal production and consumption practices within the context of labor migration from the Republic of Dagestan to the Arctic and subarctic cities of the Yamalo-Nenets and Khanty-Mansi Autonomous Okrugs, where Muslims constitute a minority. Drawing on interdisciplinary perspectives, including the anthropology of nutrition, the material turn of social sciences, the anthropology of Islam, the anthropology of infrastructure, and the anthropology of migrant communities, the article examines the dynamics of halal market formation and operation in these regions. It investigates issues such as certification processes, sources of authority, the role of the sending society, and the integration of halal consumption within the broader urban consumer landscape of non-Muslim communities. Furthermore, the study highlights the significance of reputation, religious commitment, and community behavior in shaping the consumption patterns of halal products, particularly in scenarios where goods are obtained from private traders rather than formal retail establishments. It underscores the importance of trust in suppliers and the religious ethos of the sending community in influencing consumer choices. Additionally, the article discusses the notion of specific territories as spaces of halal consumption and how the development of halal infrastructure can be perceived as a religious practice. Moreover, it explores the multifaceted motivations behind preference for halal products, revealing that while religious adherence is a significant factor, consumer decisions are also influenced by concerns for natural and ethical food choices, thereby expanding the halal market beyond Muslim consumers.